2021
DOI: 10.1007/s00404-021-06350-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epididymal sperm cryopreservation on neonatal birthweight following PESA-ICSI

Abstract: Purpose: To compare the neonatal birthweight of singletons derived from ICSI cycles with fresh or frozenthawed epididymal sperm in patients with obstructive azoospermia Methods: A total of 436 singletons derived from ICSI cycles with fresh (n=220) or frozen-thawed (n=216) epididymal sperm in obstructive azoospermia evaluated from 2012 to 2018 in the retrospective study. Multivariate generalized linear model was used to analyze the association between epididymal sperm cryopreservation and neonatal birthweight.R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
0
1
Order By: Relevance
“…To date, there few studies on the effect of frozen testicular sperm on neonatal outcomes following TESA-ICSI. Contrary to our findings, Cai et al evaluated 436 singletons conceived from ICSI cycles with fresh or frozen-thawed epididymal sperm in OA, and found that the birthweight of newborns after ICSI using frozen epididymal sperm was significantly lower than that from fresh epididymal sperm (20). However, in our present study, there was a similar result of gender ratio, average newborn birthweight, and Apgar scores in the two groups.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, there few studies on the effect of frozen testicular sperm on neonatal outcomes following TESA-ICSI. Contrary to our findings, Cai et al evaluated 436 singletons conceived from ICSI cycles with fresh or frozen-thawed epididymal sperm in OA, and found that the birthweight of newborns after ICSI using frozen epididymal sperm was significantly lower than that from fresh epididymal sperm (20). However, in our present study, there was a similar result of gender ratio, average newborn birthweight, and Apgar scores in the two groups.…”
Section: Discussioncontrasting
confidence: 99%